2018
DOI: 10.2298/pan130913026a
|View full text |Cite
|
Sign up to set email alerts
|

A flexible nonlinear inference to Okun’s law for Turkish economy in the last decade

Abstract: The study applies the flexible nonlinear inference approach of James D. Hamilton (2001) to investigate the relationship between cyclical components of unemployment and output in the Turkish economy where the unemployment rate remains at double digits despite the relatively stable economic environment over the last decade. The paper shows that economic expansion and contraction terms have an asymmetric effect on cyclical unemployment in Turkey. Moreover, the study identifies a specific range for the output gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 26 publications
1
2
0
Order By: Relevance
“…Mihajlovic uses the example of South East Europe, where Okun's coefficient has an asymmetric effect in five out of eight countries, suggesting that the unemployment effect is more pronounced in economic downturns than in upturns ( 39 ). This is supported by the data for Turkey and Mexico ( 40 , 41 ).…”
Section: Literature Review and Research Hypothesissupporting
confidence: 79%
“…Mihajlovic uses the example of South East Europe, where Okun's coefficient has an asymmetric effect in five out of eight countries, suggesting that the unemployment effect is more pronounced in economic downturns than in upturns ( 39 ). This is supported by the data for Turkey and Mexico ( 40 , 41 ).…”
Section: Literature Review and Research Hypothesissupporting
confidence: 79%
“…The study also concluded that the impacts of economic expansion on unemployment are smaller as compared to economic contraction. These findins are consistant with Arabaci and Arabaci (2018). Louail and Riache (2019) have also analyzed the asymmetric nature of okuns Law in case of developing and particularly for Saudi Arabia.…”
mentioning
confidence: 85%
“…The study states that the Okun coefficient is significantly differencing in expansion and contraction regimes. Arabacı & Arabacı (2018) studied the non-linear structure in Okun's law by means of the unemployment gap and real GDP gap series. Based on the study, it is stated that the contraction and expansion periods of the economy have an asymmetric effect on unemployment in the period 2001-2012 for Turkey.…”
Section: Literature Reviewmentioning
confidence: 99%